Nazir Akbarabadi’s Poetry: An Analytical Study - Majeed, Zahid; Subhani, Mamuna; Begum, Kashfa (sourcecoder, 2023)
Urdu literature is rich in poetry and divided into different periods. Poetry is usually about beauty and love. Nazir Akbarabadi is a famous classical poet of Urdu literature. However, commentators and most critics of the 19th century ignored Nazir’s poetry and mentioned its vulgarity, technical errors, and flaws. Staying away from the atmosphere of King’s poetry, instead of considering the poetic taste of a certain class in the selection of themes and their expression, he kept an eye on the understanding and taste of the common people. He best portrays his era and is the best example of this kind. The detailed portraiture in our classical literature Nazir Akbarabadi made people aware of realism through his poetry.